Pengembangan multimedia interaktif website dengan model Problem Based Learning pada Materi Hukum Pascal - Citra Leonie Citra Leonie; Indri Astuti; Haratua Tiur Maria (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
Pascal's Law is one of the materials students must master in learning science. 36% of students' learning outcomes on Pascal's law did not reach the KKM, namely 71. So, there is a need for efforts to increase understanding of Pascal's law concepts, one of which is to develop learning multimedia. This study aims to produce an interactive multimedia website with a problem based learning model on Pascal's law material. Using the Research and Development (R&D) method with the Dick, Carey, & Carey development model. This research and development resulted in the product "Mobil Pascal 8". The research was conducted at SMP Negeri 9 Simpang Hilir with 40 class VIII students as research subjects. In this study involved 9 validators, design experts, media, and materials. Data were analyzed qualitatively and quantitatively. From the results of data analysis (in the range of values 1-5) this interactive multimedia website is declared "valid". Thus the analysis of empirical test data with individual test procedures, small groups, and field tests on 28 students, shows "very happy" using interactive multimedia websites with an average of 91.29%. As for the effectiveness test of the multimedia website, with the criteria of students' attitudes towards the multimedia website, and the pre-test and post-test scores involving 28 students it turned out that there was a significant difference with a sig (2-tailed) value of 0.000. Sig value (2- tailed) < 0.05, it is declared valid and effective.